2006
DOI: 10.1002/mrd.20511
|View full text |Cite
|
Sign up to set email alerts
|

Strongylocentrotus drobachiensis oocytes maintain a microtubule organizing center throughout oogenesis: Implications for the establishment of egg polarity in sea urchins

Abstract: Although it has been known for over a century that sea urchin eggs are polarized cells, very little is known about the mechanism responsible for establishing and maintaining polarity. Our previous studies of microtubule organization during sea urchin oogenesis described a cortical microtubule-organizing center (MTOC) present during germinal vesicle (GV) migration in large oocytes. This MTOC was localized within the future animal pole of the mature egg. In this study we have used electron microscopy and immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Echinoderms are an exception to centriole elimination in early prophase I arrest, because most centrioles are eliminated through extrusion within the polar bodies during both of the meiotic divisions, with a last centriole being eliminated after meiosis exit (8). Remarkably, echinoderm centrioles are surrounded by PCM (g-tubulin and pericentrin) in all stages of oogenesis (43), which may protect them, further supporting the generality of a PCMdependent centriole maintenance mechanism. It is also known that Polo substrate phosphorylation is important, both for their localization and to reinforce Polo's own localization at the centrosome, in a positive feedback loop (26).…”
Section: Discussionmentioning
confidence: 90%
“…Echinoderms are an exception to centriole elimination in early prophase I arrest, because most centrioles are eliminated through extrusion within the polar bodies during both of the meiotic divisions, with a last centriole being eliminated after meiosis exit (8). Remarkably, echinoderm centrioles are surrounded by PCM (g-tubulin and pericentrin) in all stages of oogenesis (43), which may protect them, further supporting the generality of a PCMdependent centriole maintenance mechanism. It is also known that Polo substrate phosphorylation is important, both for their localization and to reinforce Polo's own localization at the centrosome, in a positive feedback loop (26).…”
Section: Discussionmentioning
confidence: 90%
“…To determine when the Dsh protein begins to accumulate in the VCD during oogenesis we carried out immunolocalization of Dsh in oocytes at different oogenic stages obtained from excised ovaries. We noted that the smallest oocytes showed low levels of Dsh expression throughout the cytoplasm and these oocytes did not have the microtubule organizing center (MTOC) that forms at the animal pole prior to meiosis and polar body formation [ 45 ] ( Figure 4A-E ). We observed that the Dsh protein begins to accumulate asymmetrically in the cortex of small oocytes and this pole was identified as the vegetal pole by the presence of an MTOC at the opposite pole of the cell ( Figure 4F-J ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, asteroid (sea star) oocytes express an AV polarity that can be identified by apical centrioles [ 65 , 66 ], an apically displaced nucleus, an absence of large vacuoles, and actin-filled spikes at the animal pole [ 66 ]. In several species of echinoids (sea urchins and sand dollars), the animal pole of oocytes can be traced by the location of the jelly canal, the site of polar body extrusion [ 44 , 56 ], and a cortical microtubule-organizing center (MTOC) [ 45 ]. Hence, the AV polarity becomes morphologically evident during oogenesis, but exactly when during this process the two poles first become polarized at the molecular level has heretofore been unclear [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as in many animals with a determinative mode, maternally accumulated germ line determinants in sea urchin eggs are associated with the cortical cytoskeleton. Although sea urchin eggs are committed to an early establishment of the animal–vegetal axis through the activation of Wnt/ β‐catenin signaling (Logan et al, ; Ettensohn, ; Egaña et al, ; Peng and Wikramanayake, ), these eggs do not establish polarity by germ plasm localization. Interestingly, Vasa can solely regulate a cell cycle and interact with the mitotic spindle during the initial cleavages of embryo (Yajima and Wessel, ).…”
Section: Discussionmentioning
confidence: 99%